2017
DOI: 10.1002/esp.4122
|View full text |Cite
|
Sign up to set email alerts
|

Large grains matter: contrasting bed stability and morphodynamics during two nearly identical experiments

Abstract: While the stabilizing function of large grains in step‐pool streams has long been recognized, the role they play in gravel‐bed streams is less clear. Most researchers have ignored the role of large grains in gravel‐bed streams, and have assumed that the median bed surface size controls the erodibility of alluvial boundaries. The experiments presented herein challenge this convention. Two experiments were conducted that demonstrate the significant morphodynamic implications of a slight change to the coarse tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 44 publications
5
62
1
Order By: Relevance
“…Specifically, the results of these experiments show that in braiding, full mobility of the median size occurs at moderate discharge but that large morphological change is associated with mobility of the coarse fractions. Limiting the mobility of the coarse fractions is then expected to reduce morphological dynamics and stabilize active braiding as shown recently by MacKenzie and Eaton ().…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the results of these experiments show that in braiding, full mobility of the median size occurs at moderate discharge but that large morphological change is associated with mobility of the coarse fractions. Limiting the mobility of the coarse fractions is then expected to reduce morphological dynamics and stabilize active braiding as shown recently by MacKenzie and Eaton ().…”
Section: Discussionmentioning
confidence: 99%
“…However, as supported by Piedra and Haynes (2011) data in this article also indicates that there is no unique equation with fixed parameters capable of describing bedload transport behaviour for gravel channels which have been exposed to differing inter-flood flow periods. This study has shown that the finest and coarsest fractions are most responsive to inter-flood flow duration and hence more realistic entrainment models might consider using these fractions to define bed stability (Carling, 1987(Carling, , 1988Ashworth and Ferguson, 1989;Eaton and Church, 2004;Tamminga et al, 2015;Eaton et al, 2017;MacKenzie and Eaton, 2017). This study has shown that the finest and coarsest fractions are most responsive to inter-flood flow duration and hence more realistic entrainment models might consider using these fractions to define bed stability (Carling, 1987(Carling, , 1988Ashworth and Ferguson, 1989;Eaton and Church, 2004;Tamminga et al, 2015;Eaton et al, 2017;MacKenzie and Eaton, 2017).…”
Section: Effect Of Inter-flood Duration On Bed Stabilitymentioning
confidence: 96%
“…The idea that channel stability is related to D 50 can be traced to the modified concept of a threshold channel proposed by Parker (), which asserts that self‐formed channels will adjust such that their banks are at the threshold of motion of D 50 , while bedload is transported along the centre of the channel. However, there is wide‐ranging evidence to suggest that mobility of D 50 has little to do with the stability of a channel (e.g., MacKenzie and Eaton, ).…”
Section: Channel Stabilitymentioning
confidence: 99%
“…). Based on our own experimental observations (e.g., MacKenzie and Eaton, ) and those documented in previous studies (Carling, , Ashworth and Ferguson, ; Eaton and Church, ; Tamminga et al , ; Eaton et al , ), we propose that the threshold between dynamically stable and unstable channels is characterized by the onset of full mobility of the D 84 , which occurs at τ 2 = 2 τ c 84 . These flows can mobilize 85% or more of the surface of a typical gravel bed, leaving only 15% of the surface grains (by area) in place (Figure ).…”
Section: Channel Stabilitymentioning
confidence: 99%
See 1 more Smart Citation